(untitled) (Sudurpaschim Spectrum, 2024)
This research paper discusses the main customs of the Rana community residing in Kailali and Kanchanpur districts of western Nepal and their social significance. The heritage of Rana culture, and rituals along with their festivals and tradition have fostered social unity which mark their agrarian lifestyle. This research aims to describe the cultural identity of Rana community and its societal contributions. A qualitative research approach was adopted for this study, utilizing the historical and observational methods for the data collection. While secondary data have been used where applicable, primary data is primarily based on interviews, active participation, and field visits. Among the sixteen main rituals found in the Hindu community, the Rana community primarily practices four significant rituals. Additionally, the Rana community uniquely practices singing mourning songs after a person’s death. The local traditions and customs prevalent in the Rana community play an essential role in fostering unity within society. Moreover, the rituals of the Rana community are mainly associated with agriculture, as it is their primary occupation.